Clinical Outcome, Return to Pre-injury Activities and Patients Satisfaction after Open ACL Reconstruction And Arthroscopic Reconstruction; An Experience From A Developing Country (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: anterior cruciate ligament (ACL); open technique; arthroscopic assisted technique; lyshlomknee score (lks); satisfaction